Analysis of Pipe Lay Barge Hafar Neptune Capability in Pipelaying Operation at Offshore North West Java Oil and Gas Field - Ignasius Krisna Armanda; Eko Budi Djatmiko; Imam Rochani (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2020)
When pipelaying activity is carried out, the most influential factor is the significant wave height. In this final project, the maximum significant wave height allowed for the PLB during the pipelaying process was analyzed with the variation of pipe diameters, which are 8 inches, 10 inches, and 12 inches; variations in the direction of coming waves namely 0o, 45o, 90o, 135o, and 180o; and stinger angle variations. First, static analysis was performed using OFFPIPE software Then, Pipe Lay Barge (PLB) Hafar Neptune modelled with MOSES software and validated with ABS MODU codes. The output was RAO from the Hafar Neptune PLB. Next, dynamic analysis was performed with OFFPIPE software, where the input is static analysis, RAO of Pipe Lay Barge Hafar Neptune, and JONSWAP wave spectrum formulation. The result of the analysis was the significant wave height that could hit the PLB when pipelaying is 3 meters for all pipe diameter variations. For variations in the direction of the wave data, the maximum Hs were 3 meters for 0 ° and 180 °, 2.5 meters for 45 °, 1.5 meters for 90 ° and 135 °.